Ileal interposition surgery targets the hepatic TGF‐β pathway, influencing gluconeogenesis and mitochondrial bioenergetics in the UCD‐T2DM rat model of diabetes. Issue 10 (15th July 2019) - Hung, Connie; Napoli, Eleonora; Ross-Inta, Catherine; Graham, James; Flores-Torres, Amanda L.; Stanhope, Kimber L.; Froment, Pascal; Havel, Peter J.; Giulivi, Cecilia
ABSTRACT: Ileal interposition (IT) is a surgical procedure that increases the delivery of incompletely digested nutrients and biliary and pancreatic secretions to the distal intestinal mucosa. Here, we investigated the metabolic impact of this intervention in 2‐mo‐old prediabetic University of California, Davis type 2 diabetes mellitus rats by assessing liver gene expression at 1.5 mo post‐IT surgery. Pathway analysis indicated decreased signaling via TGF‐β/Smad (a family of proteins named mothers against decapentaplegic homologs), peroxisome proliferator‐activated receptor (PPAR), and PI3K‐Akt‐AMPK–mechanistic target of rapamycin, likely targeting hepatic stellate cells because differentiation and activation of these cells is associated with decreased signaling via PPAR and TGF‐β/Smad. IT surgery up‐regulated the expression of genes involved in regulation of cholesterol and terpenoid syntheses and down‐regulated those involved in glycerophospholipid metabolism [including cardiolipin (CL)], lipogenesis, and gluconeogenesis. Consistent with the down‐regulation of the hepatic CL pathway, IT surgery produced a metabolic switch in liver, kidney cortex, and fat depots toward decreased mitochondrial fatty acid β‐oxidation, the process required to fuel high energy–demanding pathways ( e.g ., gluconeogenesis and glyceroneogenesis), whereas opposite effects were observed in skeletal and cardiac muscles. This study demonstrates for the first time the presence of metabolic pathways that complement the effects of IT surgery to maximize its benefits and potentially identify similarly effective, durable, and less invasive therapeutic options for metabolic disease, including inhibitors of TGF‐β signaling.—Hung, C., Napoli, E., Ross‐Inta, C., Graham, J., Flores‐Torres, A. L., Stanhope, K. L., Froment, P., Havel, P. J., Giulivi, C. Ileal interposition surgery targets the hepatic TGF‐β pathway, influencing gluconeogenesis and mitochondrial bioenergetics in the UCD‐T2DM rat model of diabetes. FASEB J. 33, 11270–11283 (2019). www.fasebj.org